Persuasive strategies in Mandela's No Easy Walk to Freedom - Faris, Ali Abdulhameed; Paramasivam, Shamala; Tan, Bee Hoon; Ahmad, Abdul Mua'ti@Zamri (Australian International Academic Centre, 2016)
Remarkable politicians are those who are skilled at communicating their ideas with a good sense of persuasion. The present paper is an endeavour to investigate the persuasive strategies of the African leader, Nelson Mandela, with reference to his address No Easy Walk to Freedom (1953). Johnstone’s (2008) framework for persuasive strategies was used for the analysis. The findings demonstrate the use of three persuasive strategies – quasilogical, presentational and analogical. Quasilogical argumentation, which is based on rationality, was made through syllogism, enthymeme and causation. To create involvement, Mandela manipulated presentational persuasion via rhetorical deixes, metaphors, repetition and alliteration. Attempting to elevate the spiritual values of his addressees in regard to the cause of liberation and freedom, Mandela employed analogical persuasion by making a reference to the Bible. Of these three strategies, quasilogical and presentational strategies were the most manipulated by Mandela in the given speech to move his audience. Logic and rationality was used to motivate his audience to receive his claims about white supremacy, andemotions mainly grief and rage were evoked to energize the course of anti-white supremacy non-violent orchestrated struggle.